Moving genome edited crops forward from the laboratory bench to the kitchen table. (April 2021) - Hong, Jun; Shi, Qian; Biswas, Sukumar; Jiang, Shang-Chuan; Shi, Jianxin
Abstract: Targeted nuclease based genome editing technology particularly clustered regularly interspaced short palindromic repeats (CRISPR) that allows to manipulate virtually almost any genomic sequences has greatly facilitated both basic and applied researches in plants. However, so far, very few of them has entered to the field and much less to the kitchen table. This review starts with a brief summary of current status of the application of genome editing in crop science and crop breeding and, then identifies technical, ethical, intellectual and other challenges for the commercialization of genome edited crops. This review explores further advances in the specificity and the prediction and detection of off-targets of CRISPR system, and highlights the importance of molecular characterization and the introduction of novel techniques such as nanotechnology to CRISPR system. Finally, this review calls for collaborative efforts in proposing principles and guidelines for moving genome edited crops forward from the laboratory bench to the kitchen table, and emphasizes the equal importance of public outreach. Highlights: Genome editing technology emerges as a key tool for crop science and crop breeding. Commercialization of genome edited crops faces great challenges. Advances in editing, delivery, and detection systems provide novel opportunities. Genome edited crops must be regulated but not in the same way as transgenic crops. Public outreach plays vital roles in the global acceptance of genome edited crops.